ANALYSIS OF VISION SCREENING AMONG KUANTAN POPULATION - Hanis Saipul, Farah; Ahmad, Norsham (International Journal of Allied Health Sciences, 2021)
Aims: The purposes of this study were to determine the percentage of failure rate from vision screening by age class and to determine the percentage of patients turn-up after referral from vision screening conducted among the Kuantan population for further eye examinations. Methodology: All the data from vision screening forms conducted from 2017 to 2019 by IIUM Kuantan Optometry Clinic were retrospectively reviewed to determine the failure rate from vision screening tests. The patients turn up after referral was determined through the appointment books. Results: Out of 1276 patients screened, 52.04% (664) were referred. Referral rate for paediatrics age class group was 51.05% (339). The referral rate for adults was 31.95% (108). 76.89% (183) of the middle age group were referred whilst 94.44% (34) of the 65 years old and older failed vision screening. The highest patients’ turn up rate was from paediatrics (30.09%), followed by the middle age group (16.94%), adult group (14.81%) and the 65 years old and older group (5.88%). In 2017 patients’ turn up rate was 10.37%, 22.32% in 2018 and 28.72% in 2019. Overall, patients’ turn up rate is low but shows positive increment over the years. Conclusion: To improve patient education and clinic efficiency for vision screening referral system to increase the number of patients’ turn up. Keywords: vision screening, referral, patients turn up, failure rate